Trends in background levels of persistent organic pollutants at Kosetice observatory, Czech Republic.1) Part I. Ambient air and wet deposition 1996-2005 - Holoubek, Ivan; Klánová, Jana; Jarkovský, Jirí; Kohoutek, Jirí (Journal of environmental monitoring, 2007)
Kosetice observatory is a facility of the Czech Hydrometeorological Institute, which is a part of the European Monitoring and Evaluation Programme (EMEP) network. Persistent organic pollutants (POPs: PCBs, DDTs, HCHs, PAHs) have been monitored in all environmental matrices using the integrated monitoring approach. Generally, the atmospheric levels of POPs in this Central European background station (mean values: 0.115 ng m(-3) for SigmaPCBs, 0.040 ng m(-3) for SigmaDDTs, 0.077 ng m(-3) for SigmaHCHs, and 17 ng m(-3) for SigmaPAHs) are significantly higher than those in other EMEP stations localized mostly in Northern and Western Europe. Long-term trends of POP concentrations in the ambient air and wet deposition are presented in this article and they show a slow decline in the last decade for most of the investigated compounds. Temporally increased levels of certain chemicals were associated with some local climatic (floods) or socio-economic (fuel prices) factors.
Keywords: časové faktory; Air Pollution; Česká republika; déšť; látky znečišťující vzduch; Rain; Czech Republic; Time Factors; Environmental Monitoring; znečištění ovzduší; Atmosphere; organické látky; Air Pollutants; monitorování životního prostředí; Organic Chemicals; atmosféra